2021
DOI: 10.1007/s00405-020-06575-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the smell loss on the quality of life and adopted coping strategies in COVID-19 patients

Abstract: Purpose To study the impact of smell loss on quality of life in patients with Coronavirus Disease 2019 , and assess the importance of olfaction before and after the loss of smell. In addition, to assess the impact of smell loss on psychological well-being and distress, and to assess coping strategies used by COVID-19 patients with smell loss. Methods This study was a cross-sectional study. A total of 487 COVID-19 positive patients with anosmia were recruited. All participants filled in the validated Multi-Clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(91 citation statements)
references
References 31 publications
(45 reference statements)
4
84
3
Order By: Relevance
“…Fiftytwo patients reported a change in their spicy taste perception, 54 in salty taste, 53 in sour taste, and 61 in sweet taste. In a comparison between men and women, COVID-19 induce taste changes and changes in taste subgroups were found to be common among women, but this needs further investigations (55,56). A possible reason for the loss of taste in COVID-19 might be due to the increasing number of ACE-2 receptors on the tongue keratinocytes and the keratinocyte cell death and slough production can block taste buds which can adversely affect taste perception (53,57).…”
Section: Covid-19 Induced Taste and Smell Lossmentioning
confidence: 99%
“…Fiftytwo patients reported a change in their spicy taste perception, 54 in salty taste, 53 in sour taste, and 61 in sweet taste. In a comparison between men and women, COVID-19 induce taste changes and changes in taste subgroups were found to be common among women, but this needs further investigations (55,56). A possible reason for the loss of taste in COVID-19 might be due to the increasing number of ACE-2 receptors on the tongue keratinocytes and the keratinocyte cell death and slough production can block taste buds which can adversely affect taste perception (53,57).…”
Section: Covid-19 Induced Taste and Smell Lossmentioning
confidence: 99%
“…Patients with Covid-19-related loss of smell have significant reductions in health-related quality of life and psychological well-being. 12 Moreover, Siegel et al . 13 found that olfactory dysfunction in older adults was associated with decreased sexual motivation and satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…We found that in three studies, QoL assessment was obtained through an online platform. Various questionnaires were used to assess the QoL, including the short version of the Questionnaire of Olfactory Disorders – Negative Statements, 8 the Multi-Clinic Smell and Taste Questionnaire, 10 the General Well-Being Schedule 10 and the 36-item Short Form Health Survey. 11 In one study, standard questions were used during clinical evaluations at the Virginia Commonwealth University of Smell and Taste Center.…”
Section: Resultsmentioning
confidence: 99%
“… 11 In one study, standard questions were used during clinical evaluations at the Virginia Commonwealth University of Smell and Taste Center. 10 …”
Section: Resultsmentioning
confidence: 99%